Evaluating the Efficacy of an Elementary Science Inservice Education Program. - Orlich, Donald C.; Ezell, James R. (Science Education)
The article discusses an evaluation of the effectiveness of elementary science in-service education programs in the U.S. The in-service programs help teachers integrate new techniques into their medium of instruction. The evaluation shows that younger teachers have significantly higher entry levels concerning process skills and inquiry techniques than older teachers. It is assumed that the success of the disservice programs is directly proportional related to the teachers perceived purpose. If the program is perceived to be relevant, then the teacher will accomplish a high level of proficiency through the in-service program.